Factors of non-persistence in civilian helicopter flight training: a narrative inquiry of pilot attrition - Wentworth, Rebecca, author; Makela, Carole J., advisor; Davies, Timothy G., committee member; Folkestad, James E., committee member; Volbrecht, Vicki J., committee member (Colorado State University. Libraries, 2012)
Previous literature on retention of student helicopter pilots shows a gap in research of civilian schools and qualitative studies. To address this gap in the literature and to help helicopter flight schools better understand the incidents of attrition from flight training, this qualitative study investigated student and school-based factors leading to attrition of helicopter pilot students from civilian training programs and how schools can intervene to help raise retention. The researcher interviewed four former helicopter pilot students of one Colorado flight school. Participants were chosen based on holding a private pilot certificate, having stated a goal of an aviation career, and having taken no training flights in the previous six months. Emergent themes from interview data include several linked to retention literature: motivation and interest, financial concerns, family care issues, need for remediation and learning style, social connections, and belonging. Also discussed are themes unique to study participants: safety, depression, responsibility, privilege, and disillusionment. Restoried interview data were scripted as a focus group. Recommendations to school leaders include continuing to research funding opportunities for students, addressing child-care needs, creating social and quasi-social student opportunities, contacting stop out students, creating an inclusive school environment, listening to students, creating individual student timelines, and helping instructors address students' learning styles. This research supports sub-baccalaureate retention research and articulates the individual nature of causes of attrition.
Keywords: helicopter pilot training; pilot training retention; retention and persistence; sub-baccalaureate education; trade and technical education; vocational training